The Use of Hedges in Females Versus Males Speeches - Lazim, Mohammad Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
This sociolinguistic study aims at investigating the linguistic concept of hedges from a sociolinguistic point of view where it manifests a comparison between the types and frequency of hedges used by males and the types and frequency of hedges used by females in a certain spoken task attributed to them in a procedural classroom work. The procedure was through recording and calculating the types and number of hedging expressions used by each group. The corpus supplying data for this study is chosen from university students. The participants were randomly selected from a fourth year university students group of different majors who study English language as a first foreign language and it is considered one of the credited subjects besides the essential subjects in their majors. A body of 36 speeches were analyzed by the researcher for the number and types of hedges used. The speeches were separated into two equal groups. Females speeches 18 / Males speeches 18. The results indicate that females are more inclined toward using hedges in their speeches than males. This study also recommends that hedges be given more attention for their benefit for language enrichment in student speeches, especially when used in argumentation and persuasion due to the adequate linguistic and rhetorical role they perform.